2021
DOI: 10.1371/journal.pone.0249488
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric modelling of grass pollen rupturing mechanisms for thunderstorm asthma prediction

Abstract: The world’s most severe thunderstorm asthma event occurred in Melbourne, Australia on 21 November 2016, coinciding with the peak of the grass pollen season. The aetiological role of thunderstorms in these events is thought to cause pollen to rupture in high humidity conditions, releasing large numbers of sub-pollen particles (SPPs) with sizes very easily inhaled deep into the lungs. The humidity hypothesis was implemented into a three-dimensional atmospheric model and driven by inputs from three meteorological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…However, recent insights into other mechanisms have suggested that lightning may underpin SPP generation. 9 The SPPs are concentrated by emergent weather events and then transported to ground level by the thunderstorm outflow tract which may be facilitated by outflows and cold down drafts. 28 The role of air pollution as an additional co-factor for TA remains uncertain, as higher levels of PM 10 (associated with acute asthma) 29 Rainfall, humidity Rainfall and humidity can lead to rupturing of pollen grains by osmotic shock [10] Lightning activity Lightning can rupture pollen grains [9] Sudden temperature changes Observational data [8] Air pollution Possible contributing factor, more research warranted [9] Climate change Potential to increase aeroallergen biomass and severe weather events [31] Aeroallergens Rye grass pollen Evidence of high skin prick or sIgE levels in affected individuals [7,46] Fungal spores Fungal sensitization in UK patients [42] Other Specific pollen associated with geographic region (eg, Olive tree) [5] Immunological Aeroallergen immunotherapy RCT of pre-seasonal grass SLIT in 34 subjects with SAR found that SLIT was protective for the 2016 Melbourne event: no SLIT patients reported an asthma exacerbation on that day, compared with 41% (7/17) on pharmacotherapy alone [5] Genetic Increasing severity if born in Australia of Asian ethnicity…”
Section: Mechanisms and Risk Factors Meteorological Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent insights into other mechanisms have suggested that lightning may underpin SPP generation. 9 The SPPs are concentrated by emergent weather events and then transported to ground level by the thunderstorm outflow tract which may be facilitated by outflows and cold down drafts. 28 The role of air pollution as an additional co-factor for TA remains uncertain, as higher levels of PM 10 (associated with acute asthma) 29 Rainfall, humidity Rainfall and humidity can lead to rupturing of pollen grains by osmotic shock [10] Lightning activity Lightning can rupture pollen grains [9] Sudden temperature changes Observational data [8] Air pollution Possible contributing factor, more research warranted [9] Climate change Potential to increase aeroallergen biomass and severe weather events [31] Aeroallergens Rye grass pollen Evidence of high skin prick or sIgE levels in affected individuals [7,46] Fungal spores Fungal sensitization in UK patients [42] Other Specific pollen associated with geographic region (eg, Olive tree) [5] Immunological Aeroallergen immunotherapy RCT of pre-seasonal grass SLIT in 34 subjects with SAR found that SLIT was protective for the 2016 Melbourne event: no SLIT patients reported an asthma exacerbation on that day, compared with 41% (7/17) on pharmacotherapy alone [5] Genetic Increasing severity if born in Australia of Asian ethnicity…”
Section: Mechanisms and Risk Factors Meteorological Factorsmentioning
confidence: 99%
“…8 In TA, these grains are ruptured by osmotic shock when exposed to high levels of moisture or by lightning activity itself, releasing thousands of sub-pollen particles (SPP) of size ≤2.5 µm respirable to the level of the lower respiratory tract, causing bronchoconstriction and the clinical presentation of TA. 9,10 Other important factors associated with TA severity include high aeroallergen levels, and meteorological factors such as the influence of annual rainfall on grassland biomass and pollen production, rapid temperature changes, high humidity, thunderstorm wind outflows, convergence line weather events, geographical location, and lightning activity itself. 4,9,11,12 The understanding of TA has required a wide range of interdisciplinary research across multiple fields in health, botany, and atmospheric sciences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These smaller size of pollen fragments permit their entry deep into the lungs. The mechanisms hypothesized for the fragmentation of pollen during thunderstorms include mechanical friction from wind gusts, electrical build up and discharge incurred during conditions of low relative humidity, and lightning strikes 14 . Air pollutants and CO 2 levels have also been shown to affect the prevalence of aeroallergens 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of strong up- and down-draught air flows within thunderstorms, the pollen grains are drawn up into the clouds and storm system. Excess moisture and humidity in the clouds then infiltrate into the pollen grains (and fungal spores) causing them to rupture (osmotic shock), releasing smaller inhalable allergens carrying granules and/or other particles [ 7 ]. The excess moisture falls as rain, which deposits micro-particles from the clouds at ground level.…”
Section: Introductionmentioning
confidence: 99%